1995
DOI: 10.1177/036354659502300109
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular Lidocaine Versus Intravenous Analgesic for Reduction of Acute Anterior Shoulder Dislocations

Abstract: We performed a prospective, randomized study to evaluate the use of injected lidocaine as an anesthetic for closed reduction of acute anterior shoulder dislocations. Thirty consecutive patients who presented at the emergency department with acute anterior shoulder dislocations were randomly placed in one of two groups. One group received an intraarticular injection of 20 ml of 1% lidocaine and the other group, intravenous injections of morphine sulfate and midazolam. The groups were compared regarding time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
1
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 11 publications
5
81
1
3
Order By: Relevance
“…9 However, despite this, mean ED length of stay for the IVS group in our study (172 minutes) was similar to previously published times (186 minutes, 3 185 minutes 8 ). However, the ED length of stay for the IAL group (197 minutes) was greater than those previously published (78 minutes, 3 75 minutes 8 ). It remains unclear why this discrepancy occurred.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…9 However, despite this, mean ED length of stay for the IVS group in our study (172 minutes) was similar to previously published times (186 minutes, 3 185 minutes 8 ). However, the ED length of stay for the IAL group (197 minutes) was greater than those previously published (78 minutes, 3 75 minutes 8 ). It remains unclear why this discrepancy occurred.…”
Section: Discussioncontrasting
confidence: 65%
“…Two studies found significantly decreased ED length of stays when IAL was used compared to IVS. 3,8 A recent systematic review of published studies comparing the two methods found that there was no difference in the success rate between IAL and IVS and the immediate complication rate was significantly higher in the IVS groups. 9 The authors concluded that IAL should be considered as a first-line therapy for shoulder reductions in the ED.…”
Section: Ré Sumémentioning
confidence: 99%
“…[10][11][12]27 The time required to achieve the reduction was also shorter in the intra-articular injection group, thus supporting the hypothesis that improved analgesia secondarily provides greater muscle relaxation, which facilitates shoulder reduction. 10 One patient was withdrawn from the control group, whereas in the group treated with intra-articular lidocaine injection, all the individuals remained until the end of the study. One previous study 10 found similar results with regard to reduction failures; however, others have reported that failures also occurred using the intra-articular injection method.…”
Section: Discussionsupporting
confidence: 53%
“…10 One patient was withdrawn from the control group, whereas in the group treated with intra-articular lidocaine injection, all the individuals remained until the end of the study. One previous study 10 found similar results with regard to reduction failures; however, others have reported that failures also occurred using the intra-articular injection method. The latter may be due to the number of patients evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Algumas medicações são contraindicadas em casos de gravidez, traumas que envolvam a monitorização do sistema nervoso central e órgãos intra-abdominais (25) . Até recentemente não havia alternativa para os analgésicos e sedativos por via oral e parenteral.…”
Section: Discussionunclassified